Kepuasan Konsumen Sebagai Dampak dari Relationship Marketing dan Kebijakan Harga - Nursatriani; Norhaedah; Ernawati, Ernawati; Nugraha Abhull Azwad (BJRM (Bongaya Journal For Research in Management), 2025)
Abstract: This study aims to analyze the influence of Relationship Marketing and date prices on customer satisfaction at Pusat Kurma dan Oleh-Oleh Haji Umroh Bin Daud Makassar. The research method used is quantitative, with data collection techniques including observation, interviews, questionnaires, and documentation. The sample consisted of 100 respondents selected through purposive sampling. The results show that, partially, Relationship Marketing positively and significantly affects customer satisfaction, with a t-value of 5.619 and a significance of 0.000. The date price variable also has a positive and significant effect, with a t-value of 14.768 and a significance of 0.000. Simultaneously, Relationship Marketing and date prices have a positive and significant effect on customer satisfaction, with an F-value of 191.561 and a significance of 0.000. The study concludes that combining effective Relationship Marketing with competitive pricing strategies can significantly enhance customer satisfaction. Therefore, the company is advised to strengthen relationships with customers and continuously adjust pricing to align with product quality. Keywords: Relationship Marketing, Price, Customer Satisfaction